Inclusive Competitiveness through AI Use in Informal SMEs: Evidence from an Extended TAM–TOE Model - Andi Naila Quin Azisah Alisyahbana; Ririn Mardhani Syakur; Andika Isma; M. Miftach Fakhri; Hajar Dewantara (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
Informal SMEs are pivotal to inclusive growth, yet capability and infrastructure constraints often limit the effective use of artificial intelligence (AI). This study examines how organizational and technological conditions shape inclusive competitiveness through AI use in Indonesian informal SMEs by extending the Technology Acceptance Model (TAM) with Technology–Organization–Environment (TOE) factors and IS-success attributes. Using a cross-sectional survey of 559 SME owners/managers and partial least squares structural equation modeling (PLS-SEM), we test pathways from organizational competence and readiness, system quality, and service quality to perceived usefulness (PU) and perceived ease of use (PEOU), and ultimately to AI usage. Results show that PU and PEOU strongly predict AI usage, and PEOU also reinforces PU. Organizational readiness and system quality significantly enhance both PU and PEOU, while organizational competence primarily strengthens PU rather than PEOU. Service quality improves PEOU but does not significantly affect PU. Mediation tests confirm that PU and PEOU transmit key organizational and technological effects to AI usage. The findings suggest that policies and managerial interventions targeting readiness-building (skills, resources, governance) and robust system design are essential to translate AI adoption into sustained utilization and more inclusive business competitiveness in the informal economy.